Lessons learned from professional development workshops on using GIS to teach geography and history in the K-12 classroom - Tabor, Lisa K.; Harrington, John A., Jr. (My University, 2014)
A GIS oriented professional development activity engaged social studies teachers with the importance of maps and graphics in teaching geography and history. With an introduction to ArcGIS Online and National Geographic Map Maker, the activity provided teachers with the ability to make their own maps and identify GIS materials for their classrooms. Conducting the workshop reinforced our belief in the need for considerable hands-on activity with participants allowed to work at their own pace. Pre- and post-event surveys showed positive gains regarding the teachers’ likelihood to include GIS based maps and graphics in teaching. The activity provided teachers with enough knowledge of GIS that they were ready to use the technology immediately.
Keywords: GIS; Geography education; History; Professional development